MEMBANGUN PEMBELAJARAN BAHASA INGGRIS BERMAKNA MELALUI STRATEGI SOSIAL EMOSIONAL DI SDN 25 KOTA BIMA - Zulkifli, Zulkifli (FASHLUNA, 2025)
The implementation of Social-Emotional Learning (SEL) in Grade 4 at SDN 25 Kota Bima aims to integrate social and emotional skills into the academic learning process. This study employs a descriptive qualitative approach to explore SEL teaching strategies and their impact on students' development. The findings indicate that integrating SEL strategies, such as the CASEL approach and collaborative activities, positively contributes to students' ability to manage emotions, build relationships, and make responsible decisions. Additionally, SEL implementation has improved students' academic performance by up to 15% and enhanced their psychological well-being. The program's success is supported by strong school leadership commitment, teacher training, parental involvement, and continuous evaluation. However, challenges such as variations in student readiness and integrating SEL into the academic curriculum require further attention. By strengthening strategies and collaboration, SEL is expected to continue providing optimal benefits for students' holistic development. ABSTRAK Penerapan pembelajaran sosial emosional (SEL) di kelas 4 SDN 25 Kota Bima bertujuan untuk mengintegrasikan keterampilan sosial dan emosional ke dalam proses pembelajaran akademik. Penelitian ini menggunakan pendekatan kualitatif deskriptif untuk mengeksplorasi strategi pengajaran SEL dan dampaknya terhadap perkembangan siswa. Hasil penelitian menunjukkan bahwa integrasi strategi SEL, seperti pendekatan CASEL dan aktivitas kolaboratif, berkontribusi positif terhadap kemampuan siswa dalam mengelola emosi, menjalin relasi, serta membuat keputusan yang bertanggung jawab. Selain itu, implementasi SEL juga meningkatkan prestasi akademik siswa hingga 15% dan memperkuat kesejahteraan psikologis mereka. Keberhasilan program ini didukung oleh komitmen kepemimpinan sekolah, pelatihan guru, keterlibatan orang tua, dan evaluasi berkelanjutan. Namun, tantangan seperti variasi kesiapan siswa dan integrasi SEL dalam kurikulum akademik masih memerlukan perhatian lebih lanjut. Dengan penguatan strategi dan kolaborasi, SEL diharapkan dapat terus memberikan manfaat optimal bagi perkembangan holistik siswa.